Forgotten Patients: Family Caregivers in Psychiatric Care Transitions and Readmission Prevention - Saverinus Suhardin; Yohana Teodosia Setu; Imakulata Bete; Camelia Bakker; Joli Riyana Nubatonis; Kurnia Bend. Yunita Pellondou (Universitas Nusa Cendana, 2026)
Introduction Psychiatric readmission remains a major challenge in mental health care, particularly in resource-limited settings where continuity of care following hospital discharge is often fragmented. Aim This study explored the role of discharge planning in preventing psychiatric readmission from the perspectives of patients, family caregivers, psychiatric hospital staff, and primary healthcare nurses in East Nusa Tenggara, Indonesia. Result The findings showed that fragmented discharge planning limited continuity of care after psychiatric discharge and increased the responsibilities of family caregivers in coordinating post-discharge care. Four interrelated themes emerged: (1) family burden extending beyond hospital discharge; (2) emotional exhaustion and psychological distress among family caregivers; (3) fragmented discharge planning and weak continuity of care following psychiatric discharge; and (4) living with limited resources. Conclusion These findings suggest that psychiatric readmission is influenced not only by patient-related factors but also by fragmented transitions of care that unintentionally transfer greater responsibility for continuity of care to family caregivers.